Shocked titanite records Chicxulub hydrothermal alteration and impact age - Timms, Nick; Kirkland, Chris; Cavosie, Aaron; Rae, A.S.P.; Rickard, William; Evans, Noreen; Erickson, Timmons; Wittmann, A.; Ferrière, L.; Collins, G.S.; Gulick, S.P.S. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
© 2020 Elsevier Ltd